Cardiovascular risk factors and cognitive decline in older people with type 2 diabetes - Feinkohl, Insa; Keller, Markéta; Robertson, Christine M.; Morling, Joanne R.; McLachlan, Stela; Frier, Brian M.; Deary, Ian J.; Strachan, Mark W.J.; Price, Jackie F. (Springer, 2015)
AIMS/HYPOTHESIS: The aim of this work was to assess the role of well-established cardiovascular risk factors in the late-life cognitive decline of patients with type 2 diabetes.